ANALYSIS OF PATENTS IN THE REMOVAL OF UNDESIRABLE TREES AND SHRUBS IN A CONTINUOUS MOVEMENT OF FOREST TRACTOR - Shegelman I. R., Vasilyev A. S., Budnik P. V. (A breakthrough in science: development strategies, 2019)
the analysis of patents of the Russian Federation in the field of removal of undesirable trees and bushes at continuous movement of the forest tractor is given for formation of knowledge base.
Keywords: непрерывное движение; деревья; кусты; trees; bushes; базовый трактор; basic tractor; continuous movement; removal of trees and bushes; удаление кустов; удаление деревьев